2016
DOI: 10.3390/f7010019
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Drivers of Patterns of Plant Diversity Along a Wide Environmental Gradient in Korean Temperate Forests

Abstract: Understanding patterns of biodiversity and their drivers along environmental gradients is one of the central topics in ecology. However, whether diversity patterns along environmental gradients differ among diversity components as well as life forms and what kind of variables control or interact to shape the diversity patterns are poorly known. This study scrutinized the distribution patterns of three plant groups with four diversity indices and evaluated the effects of regional area, topography, topographic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This pattern may also indicate the indirect impact of altitudinal gradients and topographic aspects on the species composition by limiting the habitat quality and suitability such as soil fertility, precipitation and temperature to support the vegetation which thereby shape the spatial structure of the community assemblages [29][30][31][32][33]11]. Moreover, our study is in congruent with the findings of the previous studies [33][34][35][36] that indicated the effect of altitude gradient on species composition. Here, the species composition may be determined by the ecological processes such as environmental filters, biotic interactions and species specific neutral mechanism properties such as dispersal limitation [20,30,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…This pattern may also indicate the indirect impact of altitudinal gradients and topographic aspects on the species composition by limiting the habitat quality and suitability such as soil fertility, precipitation and temperature to support the vegetation which thereby shape the spatial structure of the community assemblages [29][30][31][32][33]11]. Moreover, our study is in congruent with the findings of the previous studies [33][34][35][36] that indicated the effect of altitude gradient on species composition. Here, the species composition may be determined by the ecological processes such as environmental filters, biotic interactions and species specific neutral mechanism properties such as dispersal limitation [20,30,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…The total species richness was greatest at lower elevation (warmer sites) as compared to the higher elevation (cooler sites). Assessment of biodiversity and their drivers along environmental gradients is one of the central topics in ecology (Lee and Chun 2016). The variation in quantitative parameters, species richness as well as forest composition among all studied RTEs may be due to difference in climatic, physiographic and edaphic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Himalayan region, elevation and climatic factors are the governing factors for regional differences in species composition (Lee and Chun 2016;Sharma et al 2016). Furthermore, it is supposed that in the event of a rise in temperature at lower elevations the movement/migration of vegetation would be toward upper elevational (Chen and Hill 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest and most fundamental topics in both biology and ecology is the determination of species diversity [1][2][3][4][5], due to its importance for biodiversity conservation and the sustainable use and planning of nature reserves and forest management [6]. Species richness, as an important component of biodiversity, provides preliminary insights into the distribution of diversity and its crucial drivers on different scales [7][8][9].…”
Section: Introductionmentioning
confidence: 99%